2013
DOI: 10.1038/mp.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the role of EP HX2 gene variants in anorexia nervosa

Abstract: Anorexia nervosa (AN) and related eating disorders are complex, multifactorial neuropsychiatric conditions with likely rare and common genetic and environmental determinants. To identify genetic variants associated with AN, we pursued a series of sequencing and genotyping studies focusing on the coding regions and upstream sequence of 152 candidate genes in a total of 1205 AN cases and 1948 controls. We identified individual variant associations in the Estrogen Receptor-ß (ESR2) gene, as well as a set of rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 72 publications
3
68
0
Order By: Relevance
“…Additionally, one of our prioritized SNPs (rs6558000) (Table S5) is located in close vicinity (9kb upstream) of the EPHX2 gene that was recently identified as a susceptibility locus to AN through candidate gene sequencing study of early-onset severe AN cases and controls. 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one of our prioritized SNPs (rs6558000) (Table S5) is located in close vicinity (9kb upstream) of the EPHX2 gene that was recently identified as a susceptibility locus to AN through candidate gene sequencing study of early-onset severe AN cases and controls. 43 …”
Section: Discussionmentioning
confidence: 99%
“…42 Recently, a sequencing and genotyping study of 152 candidate genes in 1205 AN cases and 1948 controls suggested a novel association of a cholesterol metabolism influencing EPHX2 gene with susceptibility to AN. 43 …”
Section: Introductionmentioning
confidence: 99%
“…Several human genetic studies have associated the polymorphs of sEH with a range of diseases (11)(12)(13)(14). Previous work demonstrated there are signifi cant differences in the specifi c activity of the SNPs using surrogate substrates ( 10,15,17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower plasma FA epoxide-to-diol ratios were observed in K55R Caucasians but not African Americans ( 38 ), suggesting that other factors besides sEH catalytic activity play a role in the pathologies associated with this SNP. There is no indication in the literature that the pathologies associated with the other SNPs resulted from altered EpFA metabolism (11)(12)(13)(14). Separately, the observation that in some tissues the concentration of sEH ( Table 3 ) is higher than its natural substrates ( 1,18,19 ) suggests that >90% inhibition of the enzyme is needed to signifi cantly alter EpFA metabolism is some tissues, such as the liver and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AGRP is the inverse agonist of melanocortins, and data suggest that melanocortin signaling may play a role in the regulation of circulating cholesterol: in rodents, inhibition of melanocortin system in the central nervous system leads to an increase in high-density lipoprotein cholesterol in a manner independent of food intake or body weight (Perez-Tilve et al, 2010). Interestingly, the top hit in the recent Price Foundation AN high-throughput sequencing study was in the EPHX2 gene, known to influence cholesterol function (Scott-Van Zeeland et al, 2013). Considering that patients with AN often present with elevated cholesterol levels (Ohwada et al, 2006; Matzkin et al, 2006; Rigaud et al, 2009; Jauregui-Garrido et al, 2012), this clinical abnormality could be at least partially a sign of a disruption in the melanocortin system.…”
Section: Discussionmentioning
confidence: 99%